"Browning" of adipose tissue – regulation and therapeutic perspectives. (October 2013) - Peschechera, Alessandro; Eckel, Juergen
Abstract Obesity is considered a worldwide health concern. Most of obesity therapies are aimed at decreasing energy intake. However, recent data suggest that increasing cellular energy expenditure could be a useful approach to reduce adiposity. Adaptive thermogenesis, a biological process within the brown fat by which energy is dissipated in mitochondria, is a great tool to increase energy expenditure. Several studies have confirmed the presence of brown adipose tissue in adult humans, whose activity may make it a target for the treatment of obesity. Differentiation of brown adipocytes could be a potent tool to promote weight loss by increasing energy expenditure. Here we review the mechanisms potentially associated with expansion and activation of brown adipose tissue, and modulation of adaptive thermogenesis. Controlling one or more of these pathways could induce a positive regulation of brown adipogenesis. A better understanding of these molecular pathways could potentially result in novel anti-obesity therapies.